2020
DOI: 10.1159/000508649
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Complications during Pregnancy Related to Parity in Women with Congenital Heart Disease

Abstract: Objective: To describe the frequency of cardiac complications during pregnancy related to parity in women with congenital heart defects. Methods: A retrospective tertiary single-center study at the Adult Congenital Heart Disease Centre that followed 307 women with congenital heart disease during the years 1997-2015 in Gothenburg, Sweden. Maternal cardiac complications were noted for each pregnancy using medical and obstetric records. The CARPREG I and modified WHO (mWHO) risk classifications were used. Twin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…The samples of this research were taken from medical records of pregnant women with cardiac disease who gave birth in RSUP Dr. Based on a previous study by Furenäs, et al, an increase in the number of parities occurred along with an increase in the proportion of cardiac complications. 12 Another previous study by Parikh, et al, suggested that the association between parity and cardiovascular disease formed a pattern resembling the letter J, with the multiparity group as the lowest risk point. 13 The The distribution of pregnancies with cardiac disease based on maternal outcomes…”
Section: Methodsmentioning
confidence: 92%
“…The samples of this research were taken from medical records of pregnant women with cardiac disease who gave birth in RSUP Dr. Based on a previous study by Furenäs, et al, an increase in the number of parities occurred along with an increase in the proportion of cardiac complications. 12 Another previous study by Parikh, et al, suggested that the association between parity and cardiovascular disease formed a pattern resembling the letter J, with the multiparity group as the lowest risk point. 13 The The distribution of pregnancies with cardiac disease based on maternal outcomes…”
Section: Methodsmentioning
confidence: 92%
“…Previous studies have shown that parity per se is not a factor regarding risk of cardiac complications during pregnancy 53 , 54 ; however, the effect of parity on long‐term cardiovascular health has not been addressed. We did not have statistical power to test if completing more pregnancies was more detrimental as compared with completing only 1 pregnancy regarding long‐term cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that women with more complex heart disease (mWHO classes III or IV) tend to have neonates affected by FGR, give birth prematurely and deliver by cesarean section more often than women with less complex heart disease. Previously, obstetric and neonatal complications have been described in northern and western Sweden but FGR have not been described in the Swedish pregnant ACHD population before [12,13]. FGR is an interesting outcome due to the association between reduced cardiac function and placental insufficiency [14,15].…”
Section: Discussionmentioning
confidence: 99%